2009
DOI: 10.1186/1755-8166-2-17
|View full text |Cite
|
Sign up to set email alerts
|

Microdeletion of 6q16.1 encompassing EPHA7 in a child with mild neurological abnormalities and dysmorphic features: case report

Abstract: BackgroundOf the fewer than 100 cases reported within the literature of constitutional deletions involving the long arm of chromosome 6, only five have been characterized using high-resolution microarray analysis. Reported 6q deletion patients show a high incidence of mental retardation, ear anomalies, hypotonia, and postnatal growth retardation.ResultsWe report a 16-month-old male presenting with developmental delay and dysmorphic features who was found by array-based comparative genomic hybridization (aCGH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 11 publications
2
55
0
Order By: Relevance
“…A recent study revealed that microdeletion of 6q16.1 encompassing EphA7 in a child is correlated with neurological abnormalities and dysmorphic features (1). This clinical case report is somewhat consistent with previous reports that EphA7 plays an important role in the development of the central nervous system.…”
Section: Introductionsupporting
confidence: 82%
“…A recent study revealed that microdeletion of 6q16.1 encompassing EphA7 in a child is correlated with neurological abnormalities and dysmorphic features (1). This clinical case report is somewhat consistent with previous reports that EphA7 plays an important role in the development of the central nervous system.…”
Section: Introductionsupporting
confidence: 82%
“…However, he had a large 6q16 deletion (14 Mb) that encompassed several developmental genes, including EPHA7. 56 In addition, none of the central nervous system abnormalities observed in this patient has been found by brainimaging studies in previously reported cases of 6q16 deletion. In one study, various brain malformations were found in 65% of patients with 6q16 deletions.…”
Section: Cytogenetic and Molecular Resultsmentioning
confidence: 40%
“…[23][24][25][26] Details on the used arrays and specific techniques are given in Supplementary Materials. FISH studies 27 and microsatellites analyses were performed following standard procedures.…”
Section: Materials and Methods Individualsmentioning
confidence: 99%